MANAGEMENT OF E-LABORATORIES – DEVELOPMENT THROUGH BUSINESS PERSPECTIVE - Mutapčić, Tarik; Cmuk, Drago; Malarić, Roman (International Journal of Computing, 2014)
This paper presents a design of a future Web based measurement laboratory, by applying new architectural approach considering the state of art of advanced technology as well as the strategy for the future business perspective. Such approach also provides a lot of solutions and applications under the real conditions covering different areas of industrial research, operational analysis and system research methods. The paper discusses the results of preliminary testing using Appreciative Inquiry methodology, that are the basis for conceiving, designing and preparing marketing aspects of an e-laboratories and m-laboratories, considering its cost-effectiveness and multifunctionality of the applied model for a wide range of users. The result of this new approach will completely optimize current “e” and “m” laboratory solutions [1]. Management through business perspective is not only technical development, it also includes educational, humanitarian, and commercial aspects.